2020
DOI: 10.1016/j.jmr.2020.106686
|View full text |Cite
|
Sign up to set email alerts
|

High Xe density, high photon flux, stopped-flow spin-exchange optical pumping: Simulations versus experiments

Abstract: Spin-exchange optical pumping (SEOP) can enhance the NMR sensitivity of noble gases by up to five orders of magnitude at Tesla-strength magnetic fields. SEOP-generated hyperpolarised (HP) 129 Xe is a promising contrast agent for lung imaging but an ongoing barrier to widespread clinical usage has been eco-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
(74 reference statements)
1
12
0
1
Order By: Relevance
“…[80] FEM models also have had success reproducing the behavior of CF-SEOP hyperpolarizers.F ink et al [82] examined small-cell systems and reported relatively good agreement with data from Shah et al, [89] who used aSEOP cell with ac ross-section of 13 cm 2 and am odest laser power of 50 W. More recent FEM models of CF-SEOP created by Burant and Schrank [83][84][85] are currently under development with the goal of better capturing all phenomena of CF-SEOP hyperpolarizers,i ncluding complexities of mass and thermal transport within different regions of CF-SEOP cells. [65]…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…[80] FEM models also have had success reproducing the behavior of CF-SEOP hyperpolarizers.F ink et al [82] examined small-cell systems and reported relatively good agreement with data from Shah et al, [89] who used aSEOP cell with ac ross-section of 13 cm 2 and am odest laser power of 50 W. More recent FEM models of CF-SEOP created by Burant and Schrank [83][84][85] are currently under development with the goal of better capturing all phenomena of CF-SEOP hyperpolarizers,i ncluding complexities of mass and thermal transport within different regions of CF-SEOP cells. [65]…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[74] Angewandte Chemie Aufsätze 22310 www.angewandte.de Rb clusters (which, if relevant, are thought to occur only in certain CF regimes). [90] Tw os uch simulations of SF-SEOP were implemented by Skinner et al [65] and validated against two experimental datasets [75,91] from the high-Xe-density,high resonant-photon-flux regime.B oth simulations provided excellent qualitative and quantitative reproduction of the Xe-rich SF-SEOP datasets,including the inverse relationship between the optimal cell temperature (T opt )a nd [Xe]. Furthermore,u nder certain conditions the simulations trended towards a" universally optimal" laser absorption when P Xe is maximized-which may help provide 1) an explanation for the experimentally observed interplay of laser linewidth, T opt ,and [Xe],inthe context of optimizing the photon-to-[Rb] ratio (mentioned above), and 2) anew way to optimize SF hyperpolarizer operation.…”
Section: Sf-seop Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperpolarized (HP) xenon-129 ( 129 Xe) MRI is a powerful MRI approach used mainly for lung imaging and for the study of lung disorders [27,28]. A hyperpolarized (HP) metastable state is produced by spin exchange optical pumping [29][30][31], and is characterized by up to 10 5 larger longitudinal magnetization compared to thermal polarization [27]. Therefore, the magnetic resonance signal of HP nuclei can be up to 10 5 times stronger than at thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Ignoring these minor thermal variations, it was possible to examine P Xe simulations for higher laser powers against various 129 Xe blends -a useful design consideration as laser power, P l , in clinical-scale SEOP polarizers currently ranges from 29 W [55] to 1.5 kW (XeBox-E10, XeMed LLC, Durham, NH). While higher P l is expected to generate higher P Xe , Figure 6 demonstrates that for each gas blend there is a point at which increasing P l delivers no significant enhancement in polarization.…”
Section: Discussionmentioning
confidence: 99%